The Decline of Child Mortality Rates in MENA in Comparative Perspective - Iqbal, Farrukh (World Bank, Washington, DC, 2015)
Although child mortality rates have declined all across the developing world over the past 40 years, they have declined the most in the Middle East and North Africa region. This quick note documents this remarkable experience both at the country and regional levels. This paper shows how child mortality rates (measured as the number of deaths of children fewer than five years of age per 1000 live births) have declined in the 17 MENA countries for which we have data for the period 1970-2010. It is clear from the figure that all MENA countries experienced substantial declines in child mortality rates over the past four decades. What also stands out from the figure is the phenomenon of convergence. The gap between countries with high mortality rates and those with low mortality rates narrowed substantially between 1970 and 2010, suggesting the former have been converging with the latter.